Enterovirus 71 Meningoencephalitis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
Seven cases of encephalitis and 5 of aseptic meningitis caused by an outbreak of enterovirus 71 (EV71) during the summer of 1997 are reported from the Otsu Municipal Hospital, Shiga, Japan.